ECOLOGICAL AND TOXICOLOGICAL ASSESSMENT OF MUNICIPAL SOLID WASTE LANDFILLS’ IMPACT ON ADJOINING AGRO-ECOSYSTEMS - Pysarenko, P.; Samoilik, M.; Dychenko, O.; Ts’ova, Yu.; Nimets, K. (Scientific Progress & Innovations, 2022)
Municipal solid waste (MSW) landfills mainly border on rural territories and can cause the deterioration of ecological and toxicological soil condition, the quality of surface and ground water, and farm products. At the same time, the issues of estimating MSW dumps’ actual impact on adjoining territories, farmlands, in particular, have not been studied sufficiently. Therefore, the main purpose of our work was to conduct ecological and toxicological assessment of MSW landfills’ effect on adjoining agro-ecosystems taking into account spatial remoteness from pollution sources. As a result of conducted assessment of MSW landfills’ effect (30 main dumps in Poltava region make up 70 % of the whole industrially-induced load) on soils of adjoining farmlands, the excess of lead maximum permissible concentration by 1.1–5.4 times on the territory of dumps was registered (47 % of the objects); by 1.1–4.3 times (13 % of landfills) at a distance of 50 m; by 1.7–2.5 times (7 % of dumps) at a distance of 100 m. The excess of mercury maximum permissible concentration made: by 1.1–5.7 times (25 % of landfills) on the territory of dumps; by 1.7–2.3 and 1.1–1.2 times, respectively, at a distance of 50 and 100 m for 7 % of MSW landfills. The excess of zinc maximum permissible concentration was the following: by 1.1–4.3 times on the territory of dumps (17 % of landfills); by 1.1–1.8 and 1.1–1.3 times – at a distance of 50 and 100 m, respectively, for 7 % of landfills. The excess of copper maximum permissible concentration made: by 1.1–4.3 times on the territory of landfills (37 % of dumps); by 1.1–1.9 times at a distance of 50 m from dumps (13 % of landfills) and by 1.1–1.4 times at a distance of 100 m from the dumps (7 % of MSW landfills). It has been determined that petroleum products’ 1.1–6.6 time excess of maximal permissible concentration on the boundary of MSW landfills is characteristic for 30 % of MSW landfills, 1.1–3.1 time excess of maximal permissible concentration is typical for 23 % of MSW landfills at a distance of 50 m, and at 100 m the excess made 1.1–1.2 times (7 % of MSW landfills). The excess of maximal permissible concentration concerning all the heavy metals and petroleum products was not registered at a distance of 200 and 500 m. Taking into account that the actual distance from the majority of MSW landfills in the region is considerably less (90 % of MSW landfills) treats arise as to the quality and amount of obtained farm products, which requires developing measures to solve these problems. The conducted studies of atmospheric air quality on the territory of MSW landfills, on the boundary with farmlands, and at a distance of 200 m enabled to find the excess of maximal permissible concentration of carbon oxide, toluene, dust, nitric dioxide. According to the results of filtrate assessment, it has been established that the excess of polluting substances’maximal permissible concentration is typical for 60 % of MSW landfills in the region, which has created additional chemical load on soil and ground water, soils, and threatens environmental and food security of the adjoining territories. The research results can be used at assessing and decreasing the negative impact of industrially polluted lands under MSW dumps on the environment.